IBM Cognos TM1 developer's certification guide fast track your way to COG-310 certification! - Miller, James D. (Packt Pub., 2011)
This book is packed with real word examples. Each major certification topic is covered in a separate chapter, which helps to make understanding of concepts easier. At the end of each chapter, you will find a variety of practice questions to strengthen and test your learning. If you are a beginner to intermediate level Cognos TM1 developer looking to add an important IBM certification to your resume but don't know where to start, this book is for you!
Online resource; title from PDF title page (Safari, viewed Aug. 20, 2012)
Keywords: IBM Cognos TM1; Computer software -- Development -- Certification; Business -- Computer programs; Management -- Computer programs; Business planning -- Computer programs; Gestion; Logiciels; COMPUTERS; Programming; Open Source; COMPUTERS; Software Development & Engineering; General; COMPUTERS; Software Development & Engineering; Tools; Business; Computer programs; Business planning; Computer programs; Management; Computer programs